Exploring proactive work behavior: a scoping review of research trends and theories - Pratista Arya Satwika; Fendy Suhariadi; Samian (Cogent Business & Management)
Research on proactive work behaviour is increasing, but previous literature reviews remain limited. This study aims to conduct a scoping review of the literature on proactive work behaviour among employees. Using the PRISMA flowchart, articles were sourced from Scopus, Web of Science, and Ebscohost. Eligible publications were empirical studies in English or Indonesian within workplace settings. A total of 196 articles were obtained, analyzed, extracted, and synthesized for the scoping review. The results show that (1) research productivity on proactive work behaviour has risen. Between 2006 and 2024, 196 studies were conducted, with a peak in 2023. China is the leading country in this research area. Methodologically, proactive work behaviour is mostly studied as an independent variable, and the use of multilevel analysis remains limited; (2) the individual task proactivity scale from Griffin et al. (2007) is the most widely used instrument in proactive work behaviour research; and (3) five major theoretical perspectives are frequently employed: social exchange theory, conservation of resources theory, social cognitive theory, self-determination theory, and the broaden-and-build theory. These findings provide a foundation for the future development of research on proactive work behaviour.